Legal and Historical Perspectives and Comparison of Legal Sources for EEC/EU Peace-Building in the Territory of the Former Yugoslavia in 1993 and European Realities in 2020 - Dagen, Tomislav (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The last peace mediation of the European Economic Community through European Political Cooperation, as well as the operationalization of the European Union’s Common Foreign and Security Policy on 1 Novemeber 1993 in the territory of the former Yugoslavia will be reflected through the Action Plan. (Juppѐ– Kinkel Plan). Such final independent attempt by the EEC/EU to establish and build peace through peace mediation will have its stronghold in legal sources. The effects of peace mediation through the Action Plan will reflect the content and reach of legal sources and resulting mechanisms from the same sources. The failure of the Action Plan will give a new dimension to the CFSP’s foreign policy action to establish and build peace among the conflicting parties through peace mediation. Accordingly, as the subject of research in this paper, the author will draw a parallel between 1993 and 2020 from a legal and historical perspective and through comparative, historical and method of analysis, and show whether, after almost three decades, since the last EEC/EU independent peace mediation effort for establishing and building peace in the former Yugoslavia, the EU, despite its desire to be a global factor in establishing and achieving peace in the world in accordance with the content and scope of the Treaty of Lisbon and other legal sources, is able to establish and build peace among the conflicting parties.